Sustainable patchouli cultivation opportunities in Lhoong Sub-District, Aceh Besar to increase land productivity [Peluang budidaya nilam berkelanjutan di Kecamatan Lhoong Aceh Besar untuk meningkatkan produktivitas lahan] - Cut Nur Ichsan; Gina Erida; Erida Nurahmi; Muthiah Hasibuan (The Institute for Research and Community Services (LPPM) Universitas Syiah Kuala (USK), 2024)
Patchouli is a source of essential oil which is a major commodity in Indonesia, especially in the Aceh region which can be a driver of the local economy. Community service in Lhoong Sub-District, Aceh Besar aims to improve patchouli cultivation through sustainable agricultural practices. Community service was conducted at the Patchouli Industry Center, Lhoong Sub-District, Aceh Besar Regency on August 13, 2024. The tools and materials used include a sprayer, conductor, bucket, eco-enzyme made from fruit peels with a ratio of sugar, fruit or vegetables, and water of 1: 4: 10, POC, and compost made from patchouli waste and surrounding agriculture, 2% baking soda in 1 L of water. Compost, POC, and eco-enzymes function as organic fertilizers while baking soda solution is a natural fungicide to control fungal diseases, such as powdery mildew. The study results showed that although the agroecological conditions in Lhoong Sub-District are suitable for patchouli cultivation, increasing soil fertility is needed to sustain patchouli productivity. Integration of organic inputs and natural disease control methods shows results that can increase the yield and quality of patchouli. However, community motivation in cultivating patchouli plants still needs to be improved, one of which is by providing education and motivation through training programs on effective cultivation techniques with internal inputs to activate the development of the agricultural sector that attracts the interest of local people, especially the younger generation. The approach used to increase the potential for organic farming practices that can increase land productivity and the local economy, ensures the sustainability of patchouli with high yields. Patchouli has a high price in the regional and global markets which can be an opportunity to improve the welfare of the Umong Seribee Village community.